2018
DOI: 10.1016/j.bja.2018.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Agitation in adults in the post-anaesthesia care unit after general anaesthesia

Abstract: Background: Agitation after general anaesthesia can lead to self-harm, violence against staff, and increased resource utilisation. We aimed to assess patient and procedural characteristics associated with this complication in adults. Methods: We identified cases of agitation (Richmond AgitationeSedation Scale score þ3 or þ4, or administration of haloperidol) in patients after general anaesthesia in the PACU from July 1, 2010 to September 30, 2016. The cases were matched 1:1 with control patients without agitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 33 publications
4
87
0
1
Order By: Relevance
“…This outcome is in concordance with the earlier observation of Kain and co-workers that, anxious children during the induction of anesthesia increased their likelihood of developing postoperative negative behavioral changes (Kain et al 1999;2004). As well as the nding that adult patient aged more than 18 years, with postoperative agitation after GA were at high risk of postoperative delirium (Fields et al 2018).…”
Section: Discussionsupporting
confidence: 91%
“…This outcome is in concordance with the earlier observation of Kain and co-workers that, anxious children during the induction of anesthesia increased their likelihood of developing postoperative negative behavioral changes (Kain et al 1999;2004). As well as the nding that adult patient aged more than 18 years, with postoperative agitation after GA were at high risk of postoperative delirium (Fields et al 2018).…”
Section: Discussionsupporting
confidence: 91%
“…In adults, the association between age and EA has varied among studies. Age was not associated with EA in a prospective observational study of 2000 patients, as well as in a case-controlled study [2,3]. In contrast, among studies that showed a relationship between age and EA, a variety of age groups were reported as risk factors for EA.…”
Section: Agementioning
confidence: 85%
“…All rights reserved. [2,3,8,18,21,[37][38][39][40][41][42][43][44] (Table 1). Here, we review some common risk factors and important issues presented in the literature.…”
Section: Proposed Risk Factors For Emergence Agitationmentioning
confidence: 99%
See 2 more Smart Citations